Quality of marital relationships in patients with diagnosis of psychotic disorders in both partners – case report - Żmuda, Diana; Orzeł-Górniak, Małgorzata; Urbańska, Anna; Olajossy, Marcin; Makara-Studzińska, Marta (Current Problems of Psychiatry, 2015)
This article is about the quality of partner relationships in marriages in which both partners have been diagnosed with psychotic disorders such as paranoid schizophrenia (F 20.0) or schizoaffective disorders of the depressive type (F 25.1). Although within the literature there are relatively precisely descriptions of interpersonal relations in couples with a mental disorder diagnosed in one of the partners [1,2,3,4], much less is known about couples diagnosed with profound psychopathological phenomena in both partners. It seems to be extremely important to analyze the functioning of this patient group with regard to their own perception of their intimate relationship. Moreover, it is as important to understand the effect of both specific and nonspecific psychopathological symptoms as these directly project upon the quality and durability of the partner relationship. The case described here is an attempt to fill in the gaps in terms of the aforementioned notions, and bring into the light, the closer interpersonal dimensions of persons with psychotic diagnoses, taking into account as well, clinical implications important for the further course of their illness.